2023
DOI: 10.1186/s12879-023-08444-0
|View full text |Cite
|
Sign up to set email alerts
|

An ecological assessment of the potential pandemic threat of Dengue Virus in Zhejiang province of China

Abstract: Background and Aim Dengue fever, transmitted by Aedes mosquitoes, is a significant public health concern in tropical and subtropical regions. With the end of the COVID-19 pandemic and the reopening of the borders, dengue fever remains a threat to mainland China, Zhejiang province of China is facing a huge risk of importing the dengue virus. This study aims to analyze and predict the current and future potential risk regions for Aedes vectors distribution and dengue prevalence in Zhejiang provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…The results further showed that the peak period for acute infectious diseases in the Tampan District was between June to December, coinciding with the rainy season in the island of Sumatra, Indonesia. Moreover, a more responsive tracking system in the specific identification process can minimize potential breeding sites, contributing to the prevention and control of mosquito habitats (Zhang et al, 2023).…”
Section: Distribution Of Dhf Patientsmentioning
confidence: 99%
“…The results further showed that the peak period for acute infectious diseases in the Tampan District was between June to December, coinciding with the rainy season in the island of Sumatra, Indonesia. Moreover, a more responsive tracking system in the specific identification process can minimize potential breeding sites, contributing to the prevention and control of mosquito habitats (Zhang et al, 2023).…”
Section: Distribution Of Dhf Patientsmentioning
confidence: 99%